MEMUDARNYA NILAI PANTANG LARANG DALAM MENJAGA ALAM PADA MASYARAKAT DESA KELUMU KABUPATEN LINGGA - Abdul Roni; Siti Arieta; Rahma Syafitri (LPPM STISIP Persada Bunda, 2024)
Value is a person's objective view based on behavior that is adjusted to the circumstances in everyday life. Abstinence is a number of provisions that should not be violated by community members, even though some people think that abstinence is a myth. Pantang larang in Kelumu Village, Lingga Regency is related to pantang larang in protecting nature where Kelumu Village has natural resources that are still maintained marked by the potential of marine resources such as fish, coral reefs and mangrove forests. With the rapid development of the times at this time, the people of Kelumu Village began to be able to adapt by using motorized vehicles and could feel the convenience in various fields of life such as education, economy, health and communication, so that with the development of the times in this era of globalization can lead to changes in the level of trust. There are some people who do not believe in all superstitions such as supernatural beings and reading spells. The descriptive qualitative research method then the data sourced from literature studies, field observations, interviews and documentation are analyzed by data reduction, data presentation and conclusion drawing stages. The results of the study, the value of pantang larang in protecting nature in the Kelumu Village community at this time has begun to fade, in this globalization era people began to believe less in the customs and culture that their ancestors believed in. Pantang larang such as zikir saman, sea defense and land defense have begun to fade. Based on the results of research that has been conducted by researchers regarding the Fading of Pantang Larang Values in Protecting Nature in the Kelumu Village Community of Lingga Regency, it can be concluded that Indonesia is the largest archipelago in the world consisting of islands. Of the three cultures there are taboos and prohibitions. Where the taboos and prohibitions have an important role in protecting the natural environment in Kelumu Village, such as prohibiting people from entering the forest, fishing, hunting, and cutting trees during the village defense ritual.